COMPARATIVE EVALUATION OF FISH PROTEIN CONCENTRATE AND FUNCTIONAL FISH PROTEIN CONCENTRATE FROM CAT FISH. - GOPAKUMAR, K; SHENOY, A VASANTH (Fishery Technology, 2017)
Fish protein concentrate and functional fish protein concentrate samples were prepared from eviscerated meat of cat fish (Tachysurus jella Day). Functional fish protein concentrate is found to be lighter, less gritty and rehydrates more rapidly than fish protein concentrate. Functional FPC is seen to have higher PER and biscuits containing it at levels of 5 and 7 percent are less hard compared to FPC.